Evolutionary Relationships among Aspergillus Species Producing Economically Important Mycotoxins - János Varga; Krisztina Rigó; Beáta Tóth; József Téren; Zofia Kozakiewicz (Food Technology and Biotechnology, 2003)
Several mycotoxins are produced by aspergilli, which contaminate our foods and feeds. Economically the most important of these mycotoxins are aflatoxins, ochratoxins and patulin. Recent studies indicate that these compounds can be produced by a number of unrelated Aspergillus species. Evolutionary relationships among sections involving these mycotoxin producing species (Aspergillus sections Circumdati, Flavi, Nigri, Fumigati and Clavati) were evaluated using phylogenetic analysis of -tubulin and ribosomal RNA gene sequences. Phylogenetically unrelated species were found to produce the same mycotoxins. For example, aflatoxins have been produced under laboratory conditions by species belonging to three different sections, while ochratoxin A (OA) and patulin have been produced by a variety of unrelated species. Based on this observation, mycotoxin-producing abilities of the isolates were lost (or gained) several times during the evolution of the genus. Previous studies revealed that biosynthetic genes of several mycotoxins are clustered in the genome, leading to the idea that these clusters could be horizontally transferred as a unit to unrelated species, leading to the biosynthesis of the same mycotoxins in phylogenetically unrelated fungi. Such a mechanism could also explain the widespread occurrence of ochratoxin and patulin production in aspergilli. The organisation of biosynthetic genes of patulin and ochratoxins is unknown. Research is in progress in our laboratory to clarify the genetic background of biosynthesis of these mycotoxins, and to develop biosynthetic gene based probes for the molecular detection of these mycotoxin producing organisms.